Development And Characterization Of Solid Lipid Nanoparticles Of Anti-Inflammatory Drug For Ocular Drug Delivery System - F Mehta, Farhad; Singh, Neha; Pandit, Vinay; Garg, Rajeev; Upadhyay, Sukirti; Rao, Rama; Kumar Ashok, Praveen; Tripathi, Kamalesh (Journal of Neonatal Surgery, 2025)
By creating and testing flurbiprofen-solid lipid nanoparticle (SLN) loaded to enhance its therapeutic activity and lower dosage frequency to aid patient compliance, this study sought to create a novel topical ocular system of flurbiprofen. Lipids and Tween 80 or Poloxamer 180 as stabilisers were used to create SLNs utilising ultrasonic and modified high shear homogenisation methods. Particle size (PS), zeta potential (ZP), polydispersity index (PI), entrapment efficiency percentage (EE %), percentage of drug content, and in-vitro drug release were all measured and recorded for the manufactured SLNs. A transmission electron microscope (TEM) was used to do the morphological analysis of the selected SLNs. An FTIR compatibility investigation was conducted. According to the in-vitro drug release data, it was evident that the rate of drug release from SLN lasted for 10 hours when compared to plain medication. This suggested that the flurbiprofen-SLN loaded was able to regulate the flurbiprofen release rate. The results showed that, in contrast to the ocular drug delivery system, FF5 offered an efficient pharmaceutical system with a regulated release.